Analysis Of Factors Influencing The Quality Of Service On Outpatient Patient Satisfaction At The Obgyn Polyclinic Of Bahagia Hospital - M.Akbar Ali Polanunu; Hairuddin K; Jangga, Jangga (Jurnal EduHealth, 2024)
The quality of a hospital as an institution that produces health service technology products certainly also depends on the quality of medical services and nursing services provided to patients. Due to the increasingly tight and sharp competition between hospitals, each hospital is required to increase its competitiveness by trying to provide satisfaction to its patients. The purpose of this study was to analyze the factors that influence the quality of service on the satisfaction of outpatients at the Obgyn polyclinic of RSU Bahagia. This type of research is a quantitative research type, through a cross-sectional study approach. The population in this study were outpatients who had received services as seen based on data on the number of patient visits in one month, which was 67 patients. The sampling technique in this study used the Purposive Sampling technique, which was 57 respondents. The results of the statistical test analysis used the chi-square test and logistic regression test. Where the results showed that there was a significant effect with (p <0.05). Accessibility variable with p 0.003 <0.05, Waiting Time variable p 0.000 <0.05, Physical Environment variable p 0.008 <0.05, Physician Consultation variable p 0.002 <0.05 have an effect on patient satisfaction. From the results of the logistic regression test, it was obtained that Waiting Time had the most effect on patient satisfaction with a t value (6.365). It is recommended that hospitals always evaluate and improve the quality of services reviewed such as waiting time, communication between health workers, and comfort of facilities so that hospital administration and management are even better.